Psychiatric symptoms of noradrenergic dysfunction: A pathophysiological view. Issue 1 (29th December 2013) - Yamamoto, Ken‐ichi; Shinba, Toshikazu; Yoshii, Mitsunobu
<x xml:space="preserve">Abstract</x> What psychiatric symptoms are caused by central noradrenergic dysfunction? The hypothesis considered in this review is that noradrenergic dysfunction causes the abnormalities in arousal level observed in functional psychoses. In this review, the psychiatric symptoms of noradrenergic dysfunction were inferred pathophysiologically from the neuroscience literature. This inference was examined based on the literature on the biology of psychiatric disorders and psychotropics. Additionally, hypotheses were generated as to the cause of the noradrenergic dysfunction. The central noradrenaline system, like the peripheral system, mediates the alarm reaction during stress. Overactivity of the system increases the arousal level and amplifies the emotional reaction to stress, which could manifest as a cluster of symptoms, such as insomnia, anxiety, irritability, emotional instability and exaggerated fear or aggressiveness (hyperarousal symptoms). Underactivity of the system lowers the arousal level and attenuates the alarm reaction, which could result in hypersomnia and insensitivity to stress (hypoarousal symptoms). Clinical data support the hypothesis that, in functional psychoses, the noradrenergic dysfunction is in fact associated with the arousal symptoms described above. The anti‐noradrenergic action of anxiolytics and antipsychotics can explain their sedative effects on the hyperarousal symptoms of these disorders. The results of animal experiments suggest that excessive stress can be a cause of long‐term noradrenergic dysfunction.